Marine boilers - Flanagan, G. T. H. (George Terence Holford) (Marine engineering series, 1990)
The aim of this revised book is to provide practical information on boilers and their associated equipment, as used at sea on steam and motor vessels. The typical examination questions posed and answered are intended as examples to help the prospective candidate to qualify as a marine engineer officer. He should endeavour to produce similiar answers based upon equipment aboard his own ship, always stressing safety factors. It includes information on welded boilers and various types of water tube boiler, and instructions on how to deal with the rotary air heater, water level alarm and consolidated type safety valve as well as notes on hydraulic testing and various aspects of survey, maintenance and operational problems.